Comorbidity of Obsessive-Compulsive Disorder and Schizophrenia in an Adolescent - Ahmad Nabil Md. Rosli; Wan Salwina Wan Ismail (Case Reports in Psychiatry)
We report a case of a girl with a history of obsessive-compulsive disorder (OCD) subsequently exhibiting psychosis. She never attained remission since the outset. Initially she seemed to be resistant to most antipsychotics, namely, risperidone, haloperidol, paliperidone, quetiapine, and clozapine. However, she later responded remarkably better to risperidone after it was reintroduced for the second time. Recognizing and understanding the various pathogenesis of OCD or obsessive-compulsive symptoms (OCS) in schizophrenia are vital in laying out plan to manage the patient effectively.